Nurse staffing models in medical‐surgical units of acute care settings: A cross‐sectional study. Issue 1 (16th December 2019) - Assaye, Ashagre Molla; Wiechula, Richard; Schultz, Timothy J.; Feo, Rebecca
Abstract: Background: Nurse staffing models have been developed across different countries to address nursing shortages and improve quality of nursing care. However, there is no published study that describes nurse staffing models in Ethiopian hospitals. Aims: To describe the existing staffing models for nursing practice in acute care units of two hospitals (one public and one private) in Ethiopia. Methods: A cross‐sectional study was conducted from July to December 2018. A self‐administered questionnaire was used to collect data such as shift patterns, hours worked, and number of patients cared for per shift. Unit‐level data on nurse staffing were collected using a checklist developed specifically for this study. Results: Fifty‐nine percent (59.9%) of participants reported that they worked six or seven days per week. On average, they worked 50 hours per week and 12% working over 60 hours per week. The number of patients they provided care for during their last shift ranged from four to 45 with an average of 13 patients. Conclusion: This study demonstrates that nurses working in acute care settings in Ethiopia are typically working more than 40 hours per week and caring for many patients per shift, which has the potential to impact patient safety. SUMMARY STATEMENT: What is already known about this topic? Nurse staffing is a critical factor affecting patient safety and nurse workforce outcomes. There are different staffing models in which staff are assigned to give care for patients in different healthcare settings but much of the research is from high‐income countries. What this paper adds? This paper describes nurse staffing in acute care settings in Ethiopia, a low‐income country. The number of patients for whom nurses provide care per shift, and the number of hours nurses provide care per week, is very high compared with other settings. Nurses work very long hours, often more than 50 hours per week. Many nurses routinely work six or seven days per week and on average nurses care for 13 patients per shift The implication of this paper: Hospital managers should ensure that working more than 40 hours or more than five days per week should not be routine. Hospital policy that addresses the maximum number of patients who receive care by one nurse is necessary. The findings of this study support the consideration of mandated nurse‐to‐patient ratios in Ethiopia.